Case reportPerineal recurrence of prostate cancer six years after trans-perineal brachytherapy - Eppinga, Wietse; Vijverberg, Peter; Moerland, Rien; Brand, Eric; Zyp, Jochem van der Voort van; Noteboom, Juus; Vulpen, Marco van (Journal of Contemporary Brachytherapy, 2014)
We report a case of perineal recurrence of prostate cancer 6 years after low- dose rate (LDR) brachytherapy for localized prostate cancer. The most common approach to treat such perineal masses, including those occurring after prior biopsy or surgery, is local excision. We report the use of stereotactic radiotherapy with volumetric modulated arc therapy (VMAT) as a novel non-invasive, potentially curative, and patient-friendly alternative to local excision.